Kohärenz der Windgeschwindigkeiten im Mesoscale über See an drei Bojen während des Jasin '79 Projektes - Finger, Thomas (1986)
In late summer of 1978 observations took place on the North Atlantic about 300km west of the Hebrides during the international experiment JASIN '78. Three spar buoys, anchored some kilometres apart each other, sent data of wind speed, wind direction, wet and dry bulb temperature of the air as well as the water temperature via telemetry to the RV "Meteor" which lay near the obersavtion area. The obtained time series of wind speed and direction were analysed by statistical means shown in the first part of this paper. Coherence analysis was used to estimate Mesoscale structures in time and distance. The second part shows details of the measurements and quality control of the JASIN data, grouping and elimination of trend by use of two different curves. Fourier transformation of the time series yields to spectra were shown. These estimations were controlled by means of their confidence intervals taking in account the degrees of freedom of the spectra. For all coherence spectra an exponential decay with increasing frequency was assumed. Frequency was made dimension free with the mean wind speed and the distance of the buoys. Calculated decay - parameters lay between 8.6 and 9.9. In the paper of Fechner and Sardemann [9] who worked on temperature structures n the same dataset, they got values from 1.5 time sfaster than the actual wind speed between the two buoys whereas Fechner and Sardemann estimated a factor of 1.4.